Pola Komunikasi Organisasi: Studi Kangguru Internasional Education Service di Aceh - Arifa Qanitah; Fakhri; Nur Anisah (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2024)
Organizational communication patterns are a system of sending messages from communicators to communicants with the aim of changing behavior, attitudes and opinions. This research aims to look further at the organizational communication patterns carried out by KIES Aceh. This research use desciptive qualitative approach. The data used in this research is primary data collected from the field through observation and in-depth interviews. Method. The number of informants used as primary data sources in this research consisted of 4 people: Director, Deputy Director, Treasurer, and Teacher. The research results show that there are 3 organizational communication patterns used by KIES, namely: formal communication patterns, informal communication patterns and socialization mechanism communication patterns. Where these three communication patterns work well at KIES.